THE IMPACT OF CONTEXTUAL FACTORS, BRAND LOYALTY AND BRAND SWITCHING ON PURCHASE DECISION OF MINERAL WATER IN CONVENIENCE STORE - Lubis, Atur Tetty; Palibutan, Cindy Karina Anggy (Bina Nusantara University, 2015)
Mineral water has become a global business and Indonesia is one of the largest countries in mineral water consumption recording an average increase of 12.3 % every year since the last five years. However, the Indonesian bottled water market seems to have reached the maturity stage of its lifecycle. Because the competitive pressure is strongly increased, bottled water producers need to revise their marketing strategies.Â This research attempts to examine whether contextual factors-individual and society-, brand loyalty and brand switching affect young adultsâ€™ decision to purchase mineral water in convenience store in Jakarta. Total of 200 valid respondents was collected by using direct intercept technique through print questionnaire. Multiple regression analysis was conducted using SPSS 17.0. The findings of this research indicated that contextual factors have a significant impact on the purchase decision of young-adults in buying mineral water. It also revealed that brand loyalty also affects their decision in purchasing the mineral water; their positive experience with one brand would assure their purchase for that particular brand again in the future. Similarly, brand switching significantly determines the purchase decision. The research finally concluded that all factors combined together simultaneously affect the purchase decision of consumers to buy mineral water in convenience stores in Jakarta.